Foliar application of silicon and the effect on wheat seed yield and quality - Segalin,Samantha Rigo (2013)
Adequate nutrients for plants are important for increasing the yield and quality of the seeds produced. The objective of this study was to evaluate foliar fertilization with silicon in wheat and its effect on seed yield and physiological quality. Treatments consisted of two silicon dosages (three and six liters silicon per hectare) and the control (no silicon) and five wheat cultivars: OR "Quartzo", OR "Ônix", Fundacep "Linhagem", Fundacep "Campo Real" and Fundacep "Horizonte". The experimental design was randomized blocks with four replications. After physiological maturity, harvesting and threshing of the seeds were done manually. Seed samples were evaluated for yield and physiological quality from the germination test, first germination count, seedling dry weight, accelerated aging, electrical conductivity, 1000 seeds and hectoliter weights. The results showed that the foliar application of silicon at the dosages tested did not affect the yield and physiological quality of the seeds produced by the wheat cultivars.